2015
DOI: 10.1530/jme-15-0185
|View full text |Cite
|
Sign up to set email alerts
|

High level of GHR nuclear translocation in skeletal muscle of a hyperplasic transgenic zebrafish

Abstract: It has been reported that nuclear translocation of growth hormone receptor (GHR) may directly activate cell proliferation in mammals and birds. However, this phenomenon has not yet been described in fish. Recently, we have developed a transgenic zebrafish that overexpresses GHR in a muscle-specific manner. Considering that this transgenic model exhibits hyperplasic muscle growth, the present work aims at verifying the relationship between GHR nuclear translocation and muscle cell proliferation. This relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This nuclear localization has particularly been observed in proliferating cells including a range of different cancers such as colorectal carcinoma, melanoma, uterine cervical neoplasms, breast cancer, and hepatocellular carcinoma. Nuclear localized GHR has been observed in a number of species such as pig ( 300 ), rat ( 299 ), and fish ( 301 ). By targeting the GHR to the nucleus by fusing a nuclear localization signal to the receptor, it was found in the absence of GH that several genes known to be involved in oncogenesis were upregulated, and further studies provided evidence that the GHR can bind to a transcriptional regulator ( 299 , 302 ).…”
Section: Ghr In Cancermentioning
confidence: 99%
“…This nuclear localization has particularly been observed in proliferating cells including a range of different cancers such as colorectal carcinoma, melanoma, uterine cervical neoplasms, breast cancer, and hepatocellular carcinoma. Nuclear localized GHR has been observed in a number of species such as pig ( 300 ), rat ( 299 ), and fish ( 301 ). By targeting the GHR to the nucleus by fusing a nuclear localization signal to the receptor, it was found in the absence of GH that several genes known to be involved in oncogenesis were upregulated, and further studies provided evidence that the GHR can bind to a transcriptional regulator ( 299 , 302 ).…”
Section: Ghr In Cancermentioning
confidence: 99%
“…This occurs in both normal cells and under pathological conditions, such as cancer (Lobie et al 1992(Lobie et al , 1994Lincoln et al 1998;Mertani et al 1998;Conway-Campbell et al 2007;Meng et al 2022;Swanson and Kopchick 2007). The phenomenon has been shown to occur in cell lines from multiple species, including humans rodents, pigs and fish (Lobie et al 1994;Mertani et al 1998;Conway-Campbell et al 2007;Figueiredo et al 2016;Lan et al 2017Lan et al , 2018Hainan et al 2018). Lobie et al reported that the full-length GHR is associated with the nucleus and that the intracellular domain was required for nuclear localisation (Lobie et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine GH possesses extensive biological activities in pigs, e.g., improving the feed efficiency, increasing the growth rate, and changing the carcass composition [ 7 9 ]. It has been demonstrated that the porcine liver is an important target of porcine growth hormone (pGH), which endogenously expresses pGHR, and studies have demonstrated that porcine hepatocytes are an important model for studying the interactions between pGH and pGHR.…”
Section: Introductionmentioning
confidence: 99%